2008
DOI: 10.1007/s00192-008-0586-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized comparison of oxybutynin, functional electrostimulation, and pelvic floor training for treatment of detrusor overactivity in women

Abstract: The purpose of this study is to compare the effectiveness of oxybutynin, functional electrostimulation (FES), and pelvic floor training (PFT) for treatment of women with detrusor overactivity. Sixty-four subjects were randomized to oxybutynin (n=22), FES (n=21), or PFT (n=21). Women were evaluated before and after completion of 12 weeks of treatment by subjective response, voiding diary, and urodynamic test. There was subjective symptomatic improvement in 77% of the women treated with oxybutynin, 52% with FES,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 20 publications
0
49
1
6
Order By: Relevance
“…Nine trials to treat urge urinary incontinence were included with total of 534 patients (25,26,(28)(29)(30)(31)(32)(33)(34). Most patients in the trials were close to 55 years of age.…”
Section: Urge Urinary Incontinencementioning
confidence: 99%
See 1 more Smart Citation
“…Nine trials to treat urge urinary incontinence were included with total of 534 patients (25,26,(28)(29)(30)(31)(32)(33)(34). Most patients in the trials were close to 55 years of age.…”
Section: Urge Urinary Incontinencementioning
confidence: 99%
“…Five trials compared IVES and anticholinergic drugs (26,(29)(30)(31)(32). All reported significant improvement related to baseline in both groups; however, Wang et al found significant improvement in IVES related to Oxybutinin and placebo.…”
Section: Urge Urinary Incontinencementioning
confidence: 99%
“…Superiority of clinical efficacy between oxybutynin and electrical stimulation (intravaginal or TENS) in controversial (Soomro et al, 2001;Wang et al, 2006), but the prevalence of electrical stimulation devices might not enough (Walsh et al, 1999). Arruda RM et al reported the effectiveness of oxybutynin, functional electrostimulation (transvaginal) and pelvic floor training for treatment of 64 women with DO after completion of 12 weeks of treatment and resulted all three treatments were equally effective for improvement rate of subjective symptoms, urgency and urodynamic cure (Arruda et al, 2008).…”
Section: Clinical Efficacymentioning
confidence: 99%
“…Arruda et al [12] stellten eine Untersuchung vor, in der an einer allerdings kleinen Patientengruppe mit Oxybutinin 2-mal 5 mg/Tag untersucht wurde gegen die funktionelle Elektrostimulation und ein Beckenbodentraining. Nach 12 Wochen zeigte sich eine gebesserte Symptomatik unter der Oxybutinin in 77%, in der Elek trostimulationsgruppe von 52% und in der Beckenbodengymnastikgruppe von 76%.…”
Section: Vergleich Der Therapienunclassified